Risk Factors For The Event Of Pediculosis Capitis In The Baturaja Orphanage, South Sumatera, Indonesia - M. Farhan Fadhillah; Chairil Anwar; Iche Andriyani Liberty (HM Publisher, 2021)
Introduction. Pediculosis capitis is a disease of the scalp caused by infestation of Pediculus humanus capitis with symptoms such as itching and sensation of movement in the hair. The purpose of this study was to determine the risk factors and incidence of pediculosis capitis in the Baturaja orphanage.Methods. This research is an analytic observational study using a cross-sectional design with field and laboratory research. The population of this study were all children in the Baturaja orphanage who met the inclusion and exclusion criteria, as many as 172 children. All children present were taken as subjects. Data obtained by questionnaires, interviews and direct observation of the sample.Results. The results of this study showed the prevalence of pediculosis capitis in the Baturaja orphanage was 19.1%. In this study, it was found that there was a significant relationship between age (p = 0.000), education (p = 0.000), the use of shared pillows (p = 0.000), the use of shared combs (p = 0.000), the use of shared towels (p = 0.000), knowledge (p = 0.000), attitudes and behavior (p = 0.000) with the incidence of pediculosis capitis. Multivariate analysis showed that the most dominant risk factor for the incidence of pediculosis capitis in the Baturaja orphanage was age (p=0.036), while behavior was a protective factor for the incidence of pediculosis capitis.Conclusion. There is a significant relationship between age, education, use of shared pillows, use of shared combs, use of shared towels, knowledge, attitudes, behavior with the incidence of pediculosis capitis. The most dominant risk factor for the incidence of pediculosis capitis in the Baturaja orphanage is age, while behavior is a protective factor for the incidence of pediculosis capitis.